Development of BeBa (News Learning) Learning Media in News Text Learning - Putri, Aldila Rahmita; Zulfa, Lilis Anifiah (UIR PRESS, 2024)
Learning news texts is one of the compulsory learning that students need to master. There are various factors that can affect the success of learning news texts. One of them is the use of learning media. This research and development aims to (1) develop BeBa (Belajar Berita) learning media in the material identifying elements of news texts for grade VIII students of SMPN 2 Sumbergempol, (2) testing the feasibility of BeBa (Belajar Berita) learning media in the material identifying elements of news texts for grade VIII students of SMPN 2 Sumbergempol. The ADDIE model is used in research and development of Beba learning media. There are two types of data obtained in this study. Qualitative data is obtained from interviews and comments or suggestions for improvement from students and validators. Quantitative data was obtained from the results of needs analysis questionnaires, material validator assessments, media validators, teacher practitioners, and student responses. The results of material validation by material experts obtained a percentage of 93.33% with the category